2007
DOI: 10.1289/ehp.10382
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Interventions Used to Reduce Exposure to House Dust and Their Effect on the Development and Severity of Asthma

Abstract: ObjectivesWe assessed whether any household dust reduction intervention has the effect of increasing or decreasing the development or severity of atopic disease.Data sourcesElectronic searches on household intervention and atopic disease were conducted in January 2007 in EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials. No date or language restriction was placed on the literature search.Data extractionWe included randomized controlled trials comparing asthma outcomes in a household inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The HEPA filters were studied in varying environmental settings. Macdonald et al studied the effectiveness of textile‐based strategies for the primary and tertiary prevention of asthma. They reported on the number of days ill due to asthma and a lung function parameter combining the FEV 1 with the peak flow .…”
Section: Evidence Supporting the Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The HEPA filters were studied in varying environmental settings. Macdonald et al studied the effectiveness of textile‐based strategies for the primary and tertiary prevention of asthma. They reported on the number of days ill due to asthma and a lung function parameter combining the FEV 1 with the peak flow .…”
Section: Evidence Supporting the Strategiesmentioning
confidence: 99%
“…Macdonald et al studied the effectiveness of textile‐based strategies for the primary and tertiary prevention of asthma. They reported on the number of days ill due to asthma and a lung function parameter combining the FEV 1 with the peak flow . Campbell and Gibson attempted to study the effects of feather bedding, but the selected trials did not meet the inclusion criteria.…”
Section: Evidence Supporting the Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses have shown multifaceted allergen remediation programs to be protective 181, 182 against the development of asthma with 20-50% reduction in odds 172, 173 , though other studies have been disappointing 77, 183 . The most protective effect was seen in children with greater than 5 years of follow-up 182 , indicating a true decrease in risk to those prone to develop atopic asthma.…”
Section: Allergen Remediationmentioning
confidence: 99%
“…The most protective effect was seen in children with greater than 5 years of follow-up 182 , indicating a true decrease in risk to those prone to develop atopic asthma. Macdonald, et al 181 found that the decrease in physician diagnosed asthma did not carry over to the outcome of parental report of wheeze raising the question of whether there was mitigation of severity rather than prevention of disease. Those without physician diagnosis may not have presented with such significant symptoms to warrant asthma diagnosis.…”
Section: Allergen Remediationmentioning
confidence: 99%